Letter from the editor (2016)
Times of change wind this year for Earth Sciences Research Journal. The hard work of the last years have resulted in a significant advance for this journal, and now we want to announce our four volumes to be published since 2016 every year. The objective of being a top-quality journal is in the North of our compass, and it will be inspiring the daily work of the people making this publication possible.Several conferences have called our journal for special issues, and we expect to fit into their requests to keep providing the users with novel contents in the earth sciences field. In this open-access issuing, there is room for all scientific papers looking for a worldwide site to publish.But not only in Earth Sciences Research Journal challenge winds are moving the kite. The petroleum market in the world is facing one of the most critical times of the history, playing on an unexpected stage where no many actors were ready for. Management of resources are in the spotlight of the political world; energy and water, as well as the environment, turned into subjects of the first line. Fracking has resulted in thousands of discussions inside and outside of the academic world.We want to encourage everyone involved in the scientific research on earth sciences to submit us their papers. Nowadays, we substantially revised every one of the works sent and pay strict attention to the review processes, reducing periods and improving experiences of authors in the editorial world. We intend to collaborate with other professional organizations interested in geology scientific communication. Find in the ESRJ a friendly hand to work with.For the volume 20, number 1, we are presenting 18 selected papers in different areas of study; original contents we hope will be of your complete usability. Comments, claims, and suggestions are always welcomed in Earth Sciences Research Journal through the mail account earthjour_fcbog@unal.edu.co.Thanks for reading and submitting valuable scientific papers.